Experiences With Governance in Three Marine Conservation Zoning Initiatives: Parameters for Assessment and Pathways Forward - Muhl, Ella-Kari; Esteves Dias, Ana Carolina; Armitage, Derek (Frontiers in Marine Science, 2020)
IIn this perspective paper, we examine the challenges of governance in three marine conservation settings where rights, access to resources and zoning intersect with changing social and ecological conditions: 1) Tsitsikamma Marine Protected Area in South Africa; 2) Marine Protected Area of the Northern Coast of São Paulo (APAMLN) in Brazil and 3) Gwaii Haanas National Marine Conservation Area Reserve in Canada. Many MPAs and related zoning initiatives are located adjacent to coastal communities that rely on marine and coastal resources for their livelihoods. Thus, processes of zoning must often address local use of natural resources which can be perceived by decision-makers and regulators as problematic. Our analysis highlights how conservation zoning intersects with the perception of diverse stakeholders regarding a range of governance dimensions, including: 1) levels of participation and compliance; 2) the clarity of zoning and conservation objectives; 3) livelihood impacts and benefits; 4) evidence of ecological and conservation benefits; and 5) the influence on sense of place. Pathways forward to address the challenges of governance associated with zoning include the importance of co-producing knowledge for more robust zoning outcomes, and situating zoning processes in a co-management context in which power and authority are more evenly distributed.